Numerical study of the influence of external heat exchanger tube fins on heat transfer in hybrid cooling tower - Madyshev Ilnur; Chetyrchinsky Yaroslav; Kharkov Vitaly; Dmitrieva Oksana; Kasimov Ruslan (EPJ Web of Conferences)
Hybrid cooling towers with a closed circuit to cool the process water are a progressive type of cooling equipment for industrial water systems. A numerical study is performed to determine the thermal characteristics of the finned outer surface of the tubes of a heat exchanger located inside the developed hybrid cooling tower operating in dry mode. During the simulations, the parameters of the circular fins of the tube are changed: the height of the fin in the range from 2 to 8 mm and the pitch of the fins from 3 to 8 mm. It was found that with an increase in the fin height and fin pitch, i.e., with increasing fin surface transfer area, the average value of heat transfer coefficient decreases, but the overall heat power improves. It was also established that replacing the circular fins of the tubes with spiral fins can increase the heat power by up to 20.2%.